2011
DOI: 10.1590/s1678-77572011000600004
|View full text |Cite
|
Sign up to set email alerts
|

Development of a CD-ROM on written language for the continuing education of elementary school teachers

Abstract: Distance education has emerged to minimize the anxiety of many professionals who need to update their knowledge, but do not have the time and opportunity to travel to educational centers.ObjectivesTo describe the development of a CD-ROM to provide distance continuing education to basic school teachers that addresses issues related to written language. Material and MethodsPreviously, a script was developed with themes related to the acquisition and development of written language. Subsequently, a technical team… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Electronic learning, including web-based learning and multimedia CD-ROMs, is commonly used. The results of a study revealed that using CD-ROM resource im-proved teachers' knowledge, and also increased their satisfaction and comfort (4).…”
Section: Introductionmentioning
confidence: 99%
“…Electronic learning, including web-based learning and multimedia CD-ROMs, is commonly used. The results of a study revealed that using CD-ROM resource im-proved teachers' knowledge, and also increased their satisfaction and comfort (4).…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing the use in the health area, the possibility of converting traditional medical education is observed, through a model where students direct their learning focus from diverse educational tools, such as: video conferences, virtual forum, virtual rooms, among others. 8,15,17 In view of the identified studies, it was observed that the methods that used the website in its development and carried out tests with users comparing the group with use of distance methodology with control groups obtained significant results for the group tested with the educational material developed. 10,18,31 The Oliveira study did not identify a significant difference in the results between the group that used the multimedia methodology and the control group, but it was well accepted by the users.…”
Section: Discussionmentioning
confidence: 99%
“…Gonçalves GR et al, 15 Developed a virtual educational proposal, using multimedia resources, aiming to innovate, dynamize and diversify spaces of communication and interaction, favoring the process of teaching autonomous and reflective learning of nurses.…”
Section: Author Location Methods Type Of Processmentioning
confidence: 99%
“…O Brasil é um país com enormes carências educacionais, neste contexto é imprescindível suprir as necessidades de educação com outras formas de aprimoramento do conhecimento (GONÇALVES et al, 2011). O modelo de educação na sociedade da informação, deve preconizar um ensino eficaz que considere o aluno como sujeito ativo e capaz de determinar o seu auto-aprendizado, além disso, favorecer a experimentação e o pensamento reflexivo (ABREU et al, 2003;CHAVES, 2007).…”
Section: Introductionunclassified